MTAP immunohistochemistry is an accurate and reproducible surrogate for CDKN2A fluorescence in situ hybridization in diagnosis of malignant pleural mesothelioma - Chapel, David B.; Schulte, Jefree J.; Berg, Kyra; Churg, Andrew; Dacic, Sanja; Fitzpatrick, Carrie; Galateau-Salle, Francoise; Hiroshima, Kenzo; Krausz, Thomas; Le Stang, Nolwenn; McGregor, Stephanie; Nabeshima, Kazuki; et al. (Modern pathology, 2020)
Ancillary studies facilitate accurate diagnosis of morphologically challenging mesothelial proliferations. The current diagnostic algorithm proceeds from BAP1 immunohistochemistry to CDKN2A fluorescence in situ hybridization. While MTAP immunohistochemistry has recently shown promise as a surrogate for CDKN2A fluorescence in situ hybridization, it has been examined in only a few single-institution studies. Furthermore, there are no published reports on interobserver agreement or interlaboratory reproducibility for MTAP immunohistochemistry. We performed MTAP immunohistochemistry on 20 benign mesothelial lesions and 99 malignant mesotheliomas from five mesothelioma centers in four countries, and each MTAP stain was independently interpreted by four pathologists. CDKN2A fluorescence in situ hybridization data were available for a subset of cases, and a subset of cases was subjected in MTAP immunohistochemistry in multiple laboratories to assess interlaboratory reproducibility. Interobserver agreement in MTAP immunostain interpretation was excellent for all mesothelial lesions (kappa: 0.85) and for malignant mesothelioma cases only (kappa: 0.82). Interlaboratory reproducibility was also excellent (kappa values for paired protocols: 0.77–0.89). MTAP loss by immunohistochemistry was 78% sensitive and 96% specific for CDKN2A homozygous deletion. MTAP immunohistochemistry is a reliable surrogate for CDKN2A fluorescence in situ hybridization in diagnosis of malignant mesothelioma. Interobserver agreement is excellent for interpretation of MTAP staining, and protocols performed in different laboratories yield concordant MTAP staining results. Rare cases with immunohistochemical MTAP loss may retain normal CDKN2A copy number, and the MTAP staining results should be correlated with clinicopathologic findings and other ancillary studies.